Social Entrepreneurship Development Technology Based on Digital Marketing Training in Sukahaji Village Micro Enterprises - Mustika, Intan Viona; Susilawati, Susilawati; Indrakentjana, Bambang (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
he development of social entrepreneurship is one of the strategies in alleviating poverty, but the current phenomenon is that many micro-enterprises are not developing. To overcome these problems, a renewable model is needed that can encourage the sustainability of entrepreneurship in micro business actors. Digital Marketing training was chosen by researchers in developing entrepreneurship for micro business actors. The purpose of this research is to apply a model of entrepreneurship development by continuing to develop the model then implement it and test the results. This research uses a qualitative approach with the PAR (Participatory Action Research) method with interview, observation and FGD (Focus Group Discussion) techniques. This research attempts to apply the Digital Marketing training model. The technology that has been implemented shows that this development model can answer the needs and improve market access for business actors. This development model is superior and effective after being implemented, because micro-entrepreneurs can develop their business in a sustainable manner by following the development of renewable technology.